Rural women empowerment through microcredit: a comparative study between a small microcredit unit of leading go (BRDB) and NGO (BRAC) in Savar Upazila - Rahman, Muhammad Mahmudur (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2020.